(untitled) (Universal International Scientific Journal, 2026)
The article scientifically and theoretically sheds light on the pedagogical and social essence of the skills of working in virtual teams in the context of globalization and digital transformation. The communicative, cognitive-active, socially responsible and reflexive components of virtual collaborative activities are systematically analyzed. Based on the experiences of distance learning, online project activities and digital professional environments, the role of virtual team work skills in increasing the socialization, independent learning and competitiveness of the individual is substantiated. The results of the study show that the formation of skills for effective work in virtual teams is an important component of the modern educational process.